2020
DOI: 10.3390/fractalfract4020017
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Model for Drying in Frame of Generalized Fractional Derivatives

Abstract: In this article, the Lewis model was considered for the soybean drying process by new fractional differential operators to analyze the estimated time in 50 ∘ C , 60 ∘ C , 70 ∘ C , and 80 ∘ C . Moreover, we used dimension parameters for the physical meaning of these fractional models within generalized and Caputo fractional derivatives. Results obtained with generalized fractional derivatives were analyzed comparatively with the Caputo fractional, integer order derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The three authors do not point to future research trends, but through this analysis, it is recommended that it be interesting to test different speed laws for drying grains and see which ones best represent the process. Other than Ozarslan and Bas (2020), the other authors do not comment on whether there is Physical meaning in their models, despite the model by Souza Matias et al (2019) presenting physical meaning according to the findings of Simpson et al (2017).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The three authors do not point to future research trends, but through this analysis, it is recommended that it be interesting to test different speed laws for drying grains and see which ones best represent the process. Other than Ozarslan and Bas (2020), the other authors do not comment on whether there is Physical meaning in their models, despite the model by Souza Matias et al (2019) presenting physical meaning according to the findings of Simpson et al (2017).…”
Section: Resultsmentioning
confidence: 94%
“…Nicolin, da Silva, et al (2018), and Souza Matias et al (2019) carried out their studies on soy drying, in addition to them Ozarslan and Bas (2020), which dimension the parameters of the model by Souza Matias et al (2019) in order to assign physical meaning to the model. Nicolin, da Silva, et al (2018), and Souza Matias et al (2019), concluded that their models, coming from the fractional mass balance, adjusted well to the data, representing the kinetic data only in the fractional‐order.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deals fractional form of projectile motion (wind-influenced) is discussed in detail. Inverse singular spectral problems are discussed in [29] by Ozarslan et al [30] discussed the Lewis model for the soybean drying process using fractional differential operators. The results are compared with Caputo fractional derivative.…”
Section: Introductionmentioning
confidence: 99%
“…In literature different form of fractional derivative are exist in them the Caputo derivative [27] is most famous and largely used by researchers. Recently, a generalized version of fractional integral and derivatives are presented in [28,29], this generalized Caputo-type derivative has been used in investigation of many physical models [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%